Antithrombotic Activity of a Novel C-Terminal Hirudin Analog in Experimental Animals - Broersma, R J; Kutcher, L W; Heminger, E F; Krstenansky, J L; Marshall, F N (Thrombosis and Haemostasis, 1991)
A synthetic hirudinsgs55-65 C-terminal fragment analog was evaluated for anticoagulant activity and in models of experimental thrombosis in mice and rats. Intravenous injection caused doserelated inhibition of thrombin and anticoagulation in rat blood samples, protection from thromboembolism in mice and inhibition of stasis-induced venous thrombosis in rats. Antithrombotic effectiveness corresponded with anticoagulant activity. Anephric animals exhibited longer duration of activity than normal animals suggesting the kidney as a major route of elimination.